"Helping the Helpers"—Making Access to Buprenorphine the New Standard of Care for Physicians in State Monitoring Programs. Issue 1 (8th January 2023) - Dwarakanath, Megana; Klipp, Stephanie
Abstract : This commentary argues that the Federation of State Medical Board's (FSMB) recommendations concerning the use of buprenorphine for physicians in their state-affiliated monitoring programs falls short of effectively permitting an evidence-based treatment for opioid use disorder. Although the FSMB acknowledges the benefits of medications for opioid use disorder and recommends that physicians who elect to start on buprenorphine receive treatment safely and privately, the FSMB is opposed to health care professionals practicing while on buprenorphine. Their rationale is based on the notion that physicians are exceptional in their ability to remain in recovery without medications for opioid use disorder and the unsupported assumption that buprenorphine causes significant cognitive impairment. This commentary contends that FSMB policy recommendations should work to destigmatize and indeed support evidence-based treatments for physicians with substance use disorders.